2020
DOI: 10.35848/1882-0786/ab84bc
|View full text |Cite
|
Sign up to set email alerts
|

Switchable noise-like square pulses generation at 1.61 μm with a record output power

Abstract: We demonstrate the generation of high-power and large-energy noise-like square pulses (NLSPs) at 1612 nm in an all-fiber dumbbell-shaped mode-locked Er:Yb co-doped double-clad fiber (EYDF) laser. Two different types of NLSPs are obtained by adjusting polarization controllers. Pulse duration encounters “saturation” phenomenon and pulse envelop becomes distorted with enough high pump power launched into oscillator for the first state. Multi-pulse unstable state and harmonic mode-locking are obtained for the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The pulse energy and width under DSR conditions can increase infinitely with increasing pump power while the amplitude remains constant [12]. Since the DSR was proposed, there are many studies about DSR [13]- [16]. During the studies, people have found another pulse mechanism, NLSPs, whose characteristics are similar to the DSR pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The pulse energy and width under DSR conditions can increase infinitely with increasing pump power while the amplitude remains constant [12]. Since the DSR was proposed, there are many studies about DSR [13]- [16]. During the studies, people have found another pulse mechanism, NLSPs, whose characteristics are similar to the DSR pulses.…”
Section: Introductionmentioning
confidence: 99%